From International Court to Community Conflict: The Unintended Consequences of the Bakassi Ruling on Inter-Community Relations in the Cross River Estuary - Ibiang Okoi; Felix Tabi Okorn (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
The 2002 International Court of Justice ruling on the Bakassi Peninsula, which ceded the territory to Cameroon, represents one of the most significant boundary decisions in post-colonial Africa. While extensively analysed for its geopolitical and legal implications, the ruling's unintended consequences on inter-community relations within Nigeria's Cross River estuary remain inadequately examined. This paper argues that the ICJ judgment triggered a cascade of secondary boundary disputes by fundamentally altering Cross River State's coastal status, creating legal ambiguity around maritime boundaries, and generating resource competition that has manifested in renewed tensions between neighbouring communities and states. Drawing on legal geography and borderland studies frameworks, the paper analyses how an international legal decision, designed to resolve a bilateral dispute, has produced complex local consequences including the Cross River-Akwa Ibom offshore oil wells conflict, heightened inter-community competition over fishing grounds and mangrove resources, and internal political fragmentation within affected communities. The research demonstrates that international boundary adjudication cannot be understood as an isolated legal event but must be recognised as a transformative force that reshapes local spatial realities, often in ways that judicial bodies neither anticipate nor address. The findings contribute to broader scholarly conversations about the relationship between international law and local lived experiences, the unintended consequences of boundary-making, and the limitations of state-centric approaches to territorial dispute resolution.